Development of a 3D in vitro human-sized model of cervical dysplasia to evaluate the delivery of ethyl cellulose-ethanol injection - Cadena, Ines A.; Adhikari, Gatha; Almer, Alyssa; Jenne, Molly; Obasi, Ndubuisi; Soria Zurita, Nicolas F.; Rochefort, Willie E.; Mueller, Jenna L.; Fogg, Kaitlin C. (Frontiers in Biomaterials Science, 2024)
Cervical cancer, the second leading cause of cancer-related death for women worldwide, remains a preventable yet persistent disease that disproportionately affects women in low and middle-income countries (LMICs). While existing therapies for treating cervical dysplasia are effective, they are often inaccessible in LMICs. Ethanol ablation is an alternative low-cost, accessible therapy that we previously enhanced into ethyl cellulose (EC)-ethanol gel formulation to improve efficacy. When seeking to evaluate EC-ethanol for cervical dysplasia, we found a paucity of relevant animal models. Thus, in this study, we developed a 3D in vitro model of cervical dysplasia featuring a central lesion of cervical cancer cells surrounded by fibroblasts and keratinocytes to enable the evaluation of ECethanol and other novel therapeutics. Our GelMA-based 3D model successfully captured the architectural complexity of cervical dysplasia, showcasing cell response and high viability. The GelMA hydrogel formulation (8.7% w/v) exhibited viscoelastic properties akin to human cervical tissue. Using micro-CT imaging, we assessed EC-ethanol injection deposition in the hydrogel, revealing retention of virtually the entire injected volume near the injection site. Finally, we evaluated the EC-ethanol injection's efficacy in eliminating cervical cancer cells. The EC-ethanol injection led to a significant decrease in cancer cell viability while preserving healthy cells in the 3D in vitro model. Taken together, our in vitro model mirrored the architecture of cervical dysplasia and demonstrated the potential of EC-ethanol for localized treatment of cervical dysplasia.